Structural, Electronic and Magnetic Properties of XYZ Type Half-Heusler Alloys (Journal of Nepal Physical Society, 2019)
The spintronic devices have played an important role in modern technological era. Heusler alloys have attracted lot of interest in spintronic applications due to their half-metallic properties predicted by band structure calculations. We investigate the electronic, magnetic and structural properties of half-Heusleralloys FeMnGe and CoMnSb using first principles based density functional theory (DFT) implemented on Tight Binding Linear Muffin-Tin Orbital within Atomic Sphere Approximation (TB-LMTO-ASA) code. The calculation reveal that CoMnSb and FeMnGe are half-metallic Ferro-magnet in nature of with magnetic moment 1.00 μB and 2.99 μB per formula unit at equilibrium lattice parameter respectively. The magnetic moment mainly originates from the strong spin polarization of d electrons of X atom and partial contribution of p electrons of Y atom. The half metallic gap of FeMnGe and CoMnSb is found to be 0.38 eV and 0.95 eV respectively. This shows that these alloys are very promising spintronic functional materials.